2010
DOI: 10.1111/j.1651-2227.2010.01935.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Apgar score and mortality in extremely preterm neonates born in the United States

Abstract: Aim-To investigate the relationship between low Apgar score and neonatal mortality in preterm neonates.Methods-Infant birth and death certificate data from the U.S. National Center for Health Statistics for 2001-2002 were analyzed. Primary outcome was 28 day mortality for 690,933 neonates at gestational ages 24-36 weeks. Mortality rates were calculated for each combination of gestational age and five-minute Apgar score. Relative risks of mortality, by high vs. low Apgar score, were calculated for each age.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
46
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 22 publications
9
46
0
9
Order By: Relevance
“…Research that evaluate perinatal factors associated with early death in preterm infants born in eight public university hospitals affiliated with the Brazilian Neonatal Research Network found that the Apgar score between 0 and 6 at the 5 th minute was strongly associated with early neonatal death (16) . This finding is confirmed by other studies, highlighting a study conducted in the USA, which showed higher correlation between low Apgar score at the 5 th minute (0 to 6) and neonatal mortality in preterm infants with gestational age of 24 to 28 weeks (17) , association also observed in this study (OR=5.72).…”
Section: Resultssupporting
confidence: 82%
“…Research that evaluate perinatal factors associated with early death in preterm infants born in eight public university hospitals affiliated with the Brazilian Neonatal Research Network found that the Apgar score between 0 and 6 at the 5 th minute was strongly associated with early neonatal death (16) . This finding is confirmed by other studies, highlighting a study conducted in the USA, which showed higher correlation between low Apgar score at the 5 th minute (0 to 6) and neonatal mortality in preterm infants with gestational age of 24 to 28 weeks (17) , association also observed in this study (OR=5.72).…”
Section: Resultssupporting
confidence: 82%
“…The highest rates of perinatal mortality were confi rmed in other studies conducted in diff erent Brazilian states (8,9,15,17) . These results did not diff er from other studies conducted in La n America, Europe and USA (16,(18)(19)(20) . In the United Kingdom in 2010, the highest rates of neonatal mortality were related to low birth weight and gesta onal age less than 31 weeks (21) .…”
Section: Discussionsupporting
confidence: 31%
“…In the U.S.A., the rela onship between Apgar score and neonatal mortality of preterm newborns, between 2001 and 2002, showed that the increased risk of neonatal anoxia (score 0-6) occurred among newborns with gesta onal age of 24-28 weeks (average of 6). In pregnancies with 30 to 36 weeks, the mean Apgar score was nine (no anoxia) (19) .…”
Section: Discussionmentioning
confidence: 99%
“…42 In our study, birth in high-activity regions was associated with a reduced risk of being born in poor condition, as measured by the Apgar scores; low Apgar scores indicate a more pronounced fetal compromise and are associated with poor outcome. 29,43 When analyzed by GA groups, all risk reductions were confined to the 22-to 24-week GA group. Among infants born alive at 22 to 24 weeks, the 1-year mortality rate was 35% in highactivity regions and 59% in lowactivity regions.…”
Section: Discussionmentioning
confidence: 99%